On the dynamic plastic response of steel membranes subjected to localised blast loading. (March 2016) - Micallef, K.; Fallah, A.S.; Curtis, P.T.; Louca, L.A.
Highlights: Analytical formulae are obtained for maximum displacement of blast-loaded membranes. For high amplitude loads, the pulse is replaced by an equivalent impulsive velocity. For low duration loads, the pulse is replaced by an equivalent impulsive velocity. Strong correlation with finite element simulation results in all cases is observed. Strain-rate sensitivity of material is not considered in the present work. Abstract: Permanent plastic deformation is expected when close-in blasts due to e.g. detonation of Improvised Explosive Devices (IED's) hit thin metallic targets. A circular thin steel plate i.e. a membrane is studied in the present work subject to a general form of a localised blast loading. The spatial shape of the pulse is fixed and different temporal shapes are investigated. Dynamic analyses are conducted and the permanent transverse displacements are found for each case. For high amplitude pulse loads of short duration, it was found that the permanent transverse displacement can be found by replacing the load by an impulse without the loss of accuracy. Excellent correlation with numerical simulations obtained from ABAQUS/Explicit is achieved. The predicted final displacements for different pulse shapes are also found to be similar, thus where membrane action is dominant, the response is insensitive to pulse shape.